A critical analysis of temperature variation in relation to urban microclimates and the post-mortem interval. Issue 1 (2nd January 2023) - Bird, Sarah; Oost, Tracy S.
Abstract: Temperature data was collected from seven citizen scientists and one expert scientist at eight study sites for a period of 29 days between January 3rd, 2021 and February 3rd, 2021 within the region of Greater Sudbury, Ontario. The purpose of the study was to determine if significant differences exist between the eight study sites and the only Environment Canada weather station for the Greater Sudbury area that could potentially cause negative influences on a PMI estimation. Ambient air temperature was collected five times daily in 3-hour intervals between the hours of 0900 h and 2100 h. Maximum and minimum daily temperatures were recorded during the 2100 h collection. ANOVA, Tukey HSD, and a t-test were performed, showing that significant differences exist between three of the study sites when they are individually compared to Environment Canada. Microclimatic effects can explain this variation and the results serve to caution forensic practitioners that relying on Environment Canada data without studying crime scene environment could lead to errors in PMI calculation.